Searching for leptoquarks in electron-photon collisions - Éboli, O. J P; Gregores, E. M. [UNESP]; Magro, M. B.; Mercadante, P. G.; Novaes, Sérgio Ferraz [UNESP] (Elsevier, 1993)
We study the production of composite scalar leptoquarks in eγ colliders, and we show that an e+e- machine operating in its eγ mode is the best way to look for these particles in e+e- collisions, due to the hadronic content of the photon.